Evaluation the Effectiveness of Training Program in Change Management for Indonesian Teachers - Putranti, Noviah Dwi; Radiana, Usman (IKIP PGRI Bojonegoro, 2025)
The purpose of the study is to evaluate the responsive continuous teacher training program's efficacy. The study provides substantive contributions to education policy makers, because the evaluation findings help improve the quality of teacher training to be more relevant and adaptive. Using quantitative research, an experimental approach, subjects were randomly selected from 40 teachers from 12 high schools in South Pontianak District which have 7,001 students, 207 study groups and 365 teachers. Validity data were collected using valid and reliable questionnaire instruments. Using both descriptive and inferential statistical methods, the gathered data was analysed, using SPSS for hypotheses. Success focuses on improving the pedagogical skills of educators. Kirkpatrick's evaluation model feedback shows that the effectiveness of the teacher training program has increased to 89.90 with a classical completeness of 90%. Teachers in the training program showed an increase in the quality of teaching.